2015
DOI: 10.3109/02652048.2015.1046518
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic acid derived compounds loaded into liposomes: antileishmanial activity, production standardisation and characterisation

Abstract: Synthetic compounds derived from cinnamic acid were tested in cultures containing the promastigote form of Leishmania amazonensis and the dimethylsulphoxide solution of B2 compound (2.0 mg/mL) led to a 92% decrease of leishmania in 96 h of treatment. Then, different liposomal systems (diameters ∼200 nm) were prepared by the extrusion method in the presence and absence of compounds studied. DSC thermograms of the liposomes in the presence of these compounds caused changes in ΔH, Tm and ΔT1/2, compared to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…3 (B)). At 45 • C (temperature above the T m ), however, the shape of titration curve was similar to other polyphenols [39,40]. This indicates that at temperatures above T m , when lipid-ordering parameter is low, EGCG can more easily penetrate the membrane and is inserted deeper inside it, just like demonstrated with the polarisation/ anisotropy studies.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…3 (B)). At 45 • C (temperature above the T m ), however, the shape of titration curve was similar to other polyphenols [39,40]. This indicates that at temperatures above T m , when lipid-ordering parameter is low, EGCG can more easily penetrate the membrane and is inserted deeper inside it, just like demonstrated with the polarisation/ anisotropy studies.…”
Section: Resultssupporting
confidence: 54%
“…3), where interactions of EGCG with DPPC lipid membranes were observed. At 25 and 35 • C (temperatures below T m of the lipids) and lower concentrations of EGCG, EGCG did not impact the membrane like most other polyphenols, for which the energy changes of the system are greatest at their first injection and begin to approach zero with each additional injection [39,40]. In this case, the change of enthalpy is decreasing from positive values (first four injections) to negative values (next four injections) and starts increasing towards zero only after 7th or 8th injection (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The compounds loaded into the liposomes led to an efficient reduction of the L. amazonensis culture at drug concentrations that were 20-, 40-and 100-fold lower than those used in the initial tests (with the drug dissolved in DMSO). Depending on the analog used, the carrier systems reduced the L. amazonensis culture by 50-80 %; the liposomes without drugs did not affect culture viability (Cury et al 2015).…”
Section: Liposomal Systems As Carriers For Bioactive Compoundsmentioning
confidence: 95%
“…In a recently published study, Cury et al (2015) introduced synthetic analogs of 3-(3,4,5-trimethoxyphenyl) propanoic acid into liposomes and subsequently demonstrated their antileishmanial activity in cultures of Leishmania amazonensis promastigotes. The liposomal systems carrying the drugs were standardized, and the composition of the liposomes favored their interaction with the parasite cells.…”
Section: Liposomal Systems As Carriers For Bioactive Compoundsmentioning
confidence: 99%
“…Another study found that synthetic cinnamic acid derivatives in liposomal formulations were more efficient than derivatives not delivered in liposomes, again demonstrating that these special formulations may increase the delivery of lipophilic compounds in L. amazonensis promastigotes [134].…”
Section: In Vitro Activity Against Promastigotesmentioning
confidence: 97%